Development of sandwich ELISA for testing bovine β-lactoglobulin allergenic residues by specific polyclonal antibody against human IgE binding epitopes. (15th July 2017) - He, Shengfa; Li, Xin; Gao, Jinyan; Tong, Ping; Chen, Hongbing
Highlights: A sandwich ELISA was developed based on an antibody specific to IgE epitopes for beta-lactoglobulin (BLG). The method is linear from 31.25 ng/mL to 8 μg/mL, and the LOD for BLG is 1.96 ng/mL. This sandwich ELISA could be applied to determine BLG allergenic residues in food. Abstract: Bovine β-lactoglobulin (BLG) is the main allergen in cows' milk, and the most commonly used method for detecting BLG is enzyme-linked immunosorbent assay (ELISA). However, antibodies used in commercial ELISA kits do not recognize specifically BLG IgE epitopes. Here, an antibody specific to IgE linear epitopes for BLG was used to develop a sandwich ELISA using a rabbit anti-BLG polyclonal antibody. The linear range for BLG detection was 31.25–8000 ng/mL and limit of detection was 1.96 ng/mL. BLG content in dairy samples was determined, and there was a good agreement between this immunoassay and reversed-phase high-performance liquid chromatography with high recovery. Additionally, BLG content in food samples had an average recovery of 104.25%. Allergenic residues were also detected in hydrolyzed infant formulas. The method developed could be a practical approach to determine BLG and its allergenic residues in food with a high degree of sensitivity, reliability and recovery.